Universal scaling of unequal-time correlation functions in ultracold Bose gases far from equilibrium - Schachner, Andreas; Piñeiro Orioli, Asier; Berges, Jürgen (Arxiv, 2016)
We explore the far-from-equilibrium dynamics of Bose gases in a universal regime associated to nonthermal fixed points. While previous investigations concentrated on scaling functions and exponents describing equal-time correlations, we compute the additional scaling functions and dynamic exponent $z$ characterizing the frequency dependence or dispersion from unequal-time correlations. This allows us to compare the characteristic condensation and correlation times from a finite-size scaling analysis depending on the system's volume.
Gesehen am 08.12.2020